IKTISYÂF AL-ISTI’ÂRAH FÎ YÂSÎN FADHÎLAH MIN DHAU NAZHARIYYAH ABD AL-QAHIR AL-JURJANI - Herdiansyah, Pradibyo; Basid, Abdul (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2019)
This study aims to reveal; 1) the structure and characteristics of the style of Isti'ârah (metaphor), 2)  causes of beauty and implications of using Isti'ârah on meaning in Yâsîn Fadhîlah based on the theoretical perspective of Abd al-Qahir al-Jurjani. Researchers use descriptive qualitative research method by narrating the analysis of the object of study. The results showed some types of structure of Isti'arah al-Jurjani in verse and Yasin Fadhilah prayer, namely Isti'ârah which gives meaning benefit, Isti'ârah in verbs and nouns, Isti'ârah which similar form similarity, Isti'ârah whose form of similarity in the form of the meaning of nature, and Isti'ârah whose form of similarity is taken from the sensory and non-sensory delusion. The characteristics of Isti'ârah in Yâsîn Fadhîlah is the appointment of short, concise, hyperbolic style in showing the greatness of God as well as the conditions and torture of the unbelievers.